Pengaruh Profitabilitas Dan Leverage Terhadap Return Saham Pada Perusahaan Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Adelia Ananda Rizky; Karnila Ali; Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study aims to determine whether there is an effect of profitability and leverage on stockreturns. Changes in stock returns can be determined by the company's financial performanceprojected in the company's financial statements using profitability and leverage ratios. Theresearch method used in this study uses documentation techniques with a quantitativeapproach. This research was conducted at banking sub-sector companies listed on theIndonesia Stock Exchange (IDX) which were recorded during the 2019-2021 period. Thesample used in this study was purposive sampling, so that the sample in this study consisted of5 companies. The analysis used in this study is the classical assumption test, namely thenormality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. To testthe hypothesis in this study using panel data regression test with the common effect modeltechnique, fixed effect model, and random effect model. Selection of the technique is done bydoing the chow test, hausman test, and lagrange multiplier test. Based on the research resultsshow that 1) There is a significant influence between profitability and stock returns. 2) Thereis a significant influence between leverage and stock returns. 3) There is an influence betweenprofitability and leverage on stock returns